2019
DOI: 10.1049/hve.2019.0074
|View full text |Cite
|
Sign up to set email alerts
|

Broadband FIR absorption spectra of low‐density polyethylene sheets containing six different antioxidants and estimation of their contents by chemometric analysis

Abstract: Antioxidants are usually added to polymeric insulating materials to suppress oxidative degradation. However, the details of antioxidant added to a polymer are often not disclosed. On the other hand, compared to mid-infrared absorption spectroscopy, terahertz (THz) absorption spectroscopy, and far-infrared (FIR) absorption spectroscopy have not been performed so often. Based on the above backgrounds, six different kinds of antioxidants were added into low-density polyethylene sheets with four different contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…FTIR is a technique for obtaining the IR absorption spectra of gases [58], which is based on the principle of applying Fourier transform to the IR light after interference. When the laser passes the gas samples, the resulting interference spectrum will change accordingly due to the absorption of energy at certain frequencies.…”
Section: Gas Decomposition Products Detection With Optical Methodsmentioning
confidence: 99%
“…FTIR is a technique for obtaining the IR absorption spectra of gases [58], which is based on the principle of applying Fourier transform to the IR light after interference. When the laser passes the gas samples, the resulting interference spectrum will change accordingly due to the absorption of energy at certain frequencies.…”
Section: Gas Decomposition Products Detection With Optical Methodsmentioning
confidence: 99%
“…From such a viewpoint, we obtained FT-FIR and THz spectra for more than seven kinds of antioxidants and reported that the two spectroscopic analyses have a potential ability to identify antioxidants even if they have similar structures. [21][22][23][24][25] Furthermore, we have demonstrated that a chemometric analysis can make the identification more reliably even if we do not know a reference spectrum of a pristine polymer with no anitioxidants. 24,25) However, we have not confirmed that the spectra we had obtained truly reflect the molecular structure of each antioxidant.…”
Section: Introductionmentioning
confidence: 92%
“…Based on the dielectric polarisation theories, the dielectric response method is widely used for the detection of water trees [7–9] and can be divided into the frequency domain method [10–12] and the time domain method [13]. Hvidsten et al.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the dielectric polarisation theories, the dielectric response method is widely used for the detection of water trees [7][8][9] and can be divided into the frequency domain method [10][11][12] and the time domain method [13]. Hvidsten et al found that the tangent value of dielectric loss angle of insulating material increased with water tree ageing and showed strong non-linear characteristics [14].…”
Section: Introductionmentioning
confidence: 99%